Recent Advancements in the Diagnosis, Prevention, and Prospective Drug Therapy of COVID-19 - Waquar Ahsan; Hassan A. Alhazmi; Hassan A. Alhazmi; Kuldeep Singh Patel; Bharti Mangla; Mohammed Al Bratty; Shamama Javed; Asim Najmi; Muhammad Hadi Sultan; Hafiz A. Makeen; Asaad Khalid; Syam Mohan; et al. (Frontiers Media S.A., 2020)
Severe acute respiratory syndrome coronavirus (CoV)-2 (SARS-CoV-2), previously called 2019 novel CoV, emerged from China in late December 2019. This virus causes CoV disease-19 (COVID-19), which has been proven a global pandemic leading to a major outbreak. As of June 19, 2020, the data from the World Health Organization (WHO) showed more than 8.7 million confirmed cases in over 200 countries/regions. The WHO has declared COVID-19 as the sixth public health emergency of international concern on January 30, 2020. CoVs cause illnesses that range in severity from the common cold to severe respiratory illnesses and death. Nevertheless, with technological advances and imperative lessons gained from prior outbreaks, humankind is better outfitted to deal with the latest emerging group of CoVs. Studies on the development of in vitro diagnostic tests, vaccines, and drug re-purposing are being carried out in this field. Currently, no approved treatment is available for SARS-CoV-2 given the lack of evidence. The results from preliminary clinical trials have been mixed as far as improvement in the clinical condition and reduction in the duration of treatment are concerned. A number of new clinical trials are currently in progress to test the efficacy and safety of various approved drugs. This review focuses on recent advancements in the field of development of diagnostic tests, vaccines, and treatment approaches for COVID-19.